1981
DOI: 10.1523/jneurosci.01-12-01426.1981
|View full text |Cite
|
Sign up to set email alerts
|

Classical conditioning in a simple withdrawal reflex in Aplysia californica

Abstract: The ability of Aplysia and other gastropod molluscs to exhibit complex behaviors that can be modified by associative learning has encouraged us to search for an elementary behavior controlled by a simple and well analyzed neural circuit that also can be modified by this type of learning. Toward that end, we have now produced classical conditioning in the defensive siphon and gill withdrawal reflex of Aplysia. We used as a conditioned stimulus (CS) a light tactile stimulus to the siphon, which produces weak sip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
166
3

Year Published

1987
1987
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 266 publications
(183 citation statements)
references
References 30 publications
9
166
3
Order By: Relevance
“…ZD7288 (100 μM) did not have significant effects on the amplitude of the initial siphon withdrawal in response to either the siphon tap CS or tail shock US. ZD7288 also did not have a significant effect on the change in response to the CS following unpaired training (F[1,44] = 1.48, NS overall and at each test), which is a nonassociative protocol that produces results intermediate between training with the CS alone (habituation) or US alone (sensitization), and can be thought of as a combination of the two (56,57). However, ZD7288 significantly reduced the difference between paired and unpaired training, or conditioning (average = 23% of control, F[1,44] = 7.26, P < 0.01 for the interaction of drug and pairing overall and P < 0.05 onetail at each test).…”
Section: Hcn Channels Contribute To Behavioral Conditioning But Notmentioning
confidence: 99%
“…ZD7288 (100 μM) did not have significant effects on the amplitude of the initial siphon withdrawal in response to either the siphon tap CS or tail shock US. ZD7288 also did not have a significant effect on the change in response to the CS following unpaired training (F[1,44] = 1.48, NS overall and at each test), which is a nonassociative protocol that produces results intermediate between training with the CS alone (habituation) or US alone (sensitization), and can be thought of as a combination of the two (56,57). However, ZD7288 significantly reduced the difference between paired and unpaired training, or conditioning (average = 23% of control, F[1,44] = 7.26, P < 0.01 for the interaction of drug and pairing overall and P < 0.05 onetail at each test).…”
Section: Hcn Channels Contribute To Behavioral Conditioning But Notmentioning
confidence: 99%
“…It should be possible to answer this question by comparing the neural mechanisms of the different forms of learning, ideally in the same preparation. The gill-and siphon-withdrawal reflex of Aplysia has been useful for such studies, because it exhibits several forms of learning including habituation, dishabituation, sensitization, and classical conditioning (Pinsker et al, 1970;Carew et al, 1971Carew et al, , 1981, and it is amenable to cellular analysis. Studies of the cellular mechanisms of learning in Aplysia have revealed both similarities and differences between the mechanisms contributing to dishabituation and sensitization (Carew et al, 1971;Wright et al, 1991;Cohen et al, 1997;Antonov et al, 1999) and also between those contributing to sensitization and classical conditioning (Hawkins et al, 1993;Antonov et al, 2001Antonov et al, , 2003Li et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In neurobiology Aplysia has been often used for investigating classical and operant conditioning (Carew & Walters & Kandel, 1981). Consider a slightly simplified classical conditioning experiment of the Aplysia's defensive withdrawal reflex.…”
Section: Simulation Of Adaptive Agent Behaviormentioning
confidence: 99%